Accelerating food and nutrition security during conflict and protracted displacement - Gilligan, Daniel O. (2018)
Daniel Gilligan IFPRI-FAO conference, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand